Pengaruh Metakognisi dan Motivasi terhadap Kemampuan Pemecahan Masalah Matematika Melalui Kreativitas Siswa Kelas VIII SMP Negeri di Kecamatan Kindang Kabupaten Bulukumba - Muhammad Ihsan (Prodi Pendidikan Matematika FTIK IAIN Palopo, 2016)
Several factors that influence students ability to solve mathematics problem are metacognition, learning motivation, and learning creativity on mathematics. Therefore, this research aimed to identify the influence level of metacognition and learning motivation toward mathematics problem solving ability through learning creativity of students. The population was students at grade VIII of public junior high school in Kindang sub district of Bulukumba. Technique of sampling was by equal size random sampling. The data were collected through questionnaire and test, and then analyzed by using descriptive statistics and SEM (Structural Equation Modeling) analysis. The result revealed that (1) there is a positive significant influence of metacognition toward learning creativity; (2) there is also a positive significant influence of learning motivation toward learning creativity; (3) the direct influence of metacognition toward mathematics problem solving ability is positive and significant; (4) the direct influence of learning motivation toward mathematics problem solving ability is positive significant; (5) there is a positive significant influence of learning creativity toward mathematics problem solving ability; (6) the indirect influence of metacognition toward mathematics problem solving ability through learning creativity is positive significant; and (7) the indirect influence of learning motivation toward mathematics problem solving ability through learning creativity is positive and significant.